Dual effects of organic solvents on chloroplast phosphoribulokinase and NADP-glyceraldehyde-3-P dehydrogenase - Wolosiuk, R.A. (1985)
Organic solvents miscible in water (cosolvents) exerted a dual effect on the activation stage of two thioredoxin-linked enzymes of the reductive pentose phosphate cycle, phosphoribulokinase and NADP-glyceraldehyde-3-P dehydrogenase, both from spinach chloroplast; the enzyme specific activity was stimulated and inhibited by low and high concentrations of alcohols, respectively. On the contrary, cosolvents inhibited the catalytic process. In the stimulation of phosphoribulokinase activation, organic solvents reduced the requirement for thioredoxin-f and changed the thiol specificity, so that monothiols became functional. The cosolvent-mediated enhancement of NADP-glyceraldehyde-3-P dehydrogenase was obtained in the absence of modulators. With both enzymes, the concentration of the organic solvents required for activation was inversely proportional to its hydrophobicity (1-butanol < 1-propanol < 2-propanol < ethanol). The present results demonstrate the participation of a new component, the enzyme microenvironment, in the regulation of thioredoxin-linked chloroplast enzymes. © 1985.